A short description of the Latvian mammal fauna - Valdis Pilats (Hystrix, the Italian Journal of Mammalogy, 1996)
Abstract Since the 17th century 74 mammal species have been recorded in Latvia. Two species have become extinct, 10 species have been observed occasionally or introduced unsuccessfully but 62 are considered as permanently occurring in Latvia. Among the latter 8 species have been introduced or have invaded Latvia. 23 species are included in the Red list.